REDD+ contribution to well-being and income is marginal: the perspective of local stakeholders - Sunderlin, William D.; Sassi, Claudio de; Ekaputri, A.D.; Light, M.; Pratama, C.D. (MDPI, 2017)
In addition to being a global strategy for reducing greenhouse gas emissions from tropical deforestation, Reducing Emission from Deforestation and Degradation (REDD+) intends to protect and improve the well-being and income of local stakeholders. The intention is to provide livelihood support in exchange for local stakeholder involvement in protecting forests. Eleven years after the launch of REDD+ at COP 11 in Montreal, the degree of success in meeting well-being and income goals is examined in six countries (Brazil, Peru, Cameroon, Tanzania, Indonesia, Vietnam) at 22 initiatives, 149 villages, and approximately 4000 households through a counter-factual approach. Half the villages and households are inside and half are outside the sphere of REDD+. Measurements are made at two points in time (2010–2012, and 2013–2014). This paper focuses on measurement of the subjective perception of local stakeholders. The study finds that REDD+ has not contributed significantly to perceived well-being and income sufficiency, in spite of the fact that most households have not only engaged with REDD+ interventions, but view them favorably. REDD+’s limited achievement to date is due to unavailability of funding, among other obstacles. Recommendations are made for enhanced attention to well-being and income sufficiency in the event that REDD+ eventually takes off.